If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 10) = 3 Reorder the terms: (10 + 4x) = 3 Remove parenthesis around (10 + 4x) 10 + 4x = 3 Solving 10 + 4x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 4x = 3 + -10 Combine like terms: 10 + -10 = 0 0 + 4x = 3 + -10 4x = 3 + -10 Combine like terms: 3 + -10 = -7 4x = -7 Divide each side by '4'. x = -1.75 Simplifying x = -1.75
| 15x-11=7x-51 | | 12x+6=6x+72 | | 11x-12=12x-9 | | 2x^3-5x+8=0 | | 6x+10=9x-5 | | X/5-75=116 | | 2y-4(-6z+3y)-5z=0 | | 12x-8=9x+25 | | 15x-4=9x+32 | | 14x-11=7x+17 | | 75-x/5=116 | | 4x-5=8x-1 | | (6+w)(4w-1)=0 | | 1/2×10h=35 | | s^2+3s=-16 | | 5x+7=12x+35 | | 6x-7/5x=3 | | 8x-10=8x-10 | | 13x-9=8x-34 | | x^2+6x = 0 | | 7b+7=42 | | 10x-12=4x+48 | | 11x+12=10x+18 | | 2x(5+3)-16= | | 3p/5=9/4 | | 2x(5+3)-4= | | 3/4-x=7 | | p=2*66+2*94 | | 6x^2*2x^2= | | i+-56=-82 | | 5x/14-11x/7= | | 2.5x=85 |